Breaking failure analysis and finite element simulation of wear-out winding hoist wire rope. (January 2019) - Chang, Xiang-dong; Peng, Yu-xing; Zhu, Zhen-cai; Gong, Xian-sheng; Yu, Zhang-fa; Mi, Zhen-tao; Xu, Chun-ming
Abstract: Surface wear is the main reason for the breaking failure of the wire rope in service, particularly in the multi-layer winding hoist system of a coal mine. Understanding the effect of wear scars on the failure and mechanical properties of the rope is the effective way to ensure the safety of multi-layer winding hoist. In this paper, the breaking failure characteristics of hoist ropes with different wear scars were investigated by the breaking tensile test. The temperature rise in the wear scar regions was obtained and analyzed. Additionally, the finite element method was used to simulate the mechanical properties of the wear-out strands subjected to tensile load. Results show that the severe plastic deformation and obvious temperature rise occur in the wear scar region. The temperature rise curves during the breaking tensile test can reflect the number and the order of the fractured strands. The wear-out outer wires fracture earlier than the internal wires, and the wires with irregular wear scar always fracture along the sliding wear direction at the location with the maximum wear depth. Additionally, the wear scar caused by left cross contact will cause stress concentration and uneven distribution, and the wear depth makes it more obvious. Graphical abstract: Highlights: The severe plastic deformation and high temperature rise first occur in the wear scar regions. The variation of temperature rise can reflect the number and the order of the fractured strands. The fracture always occurs at the location with the maximum wear depth for irregular wear scar. There is little effect of the wear scar on the fracture of the internal undamaged strand wires. There is obvious stress concentration and uneven stress distribution in the wear scar regions.